ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNA DALAM PEMANFAATAN LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA PEKANBARU - Fetriwahyuni, Rozi; Desmiyawati, Desmiyawati; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to test the effect of educational level, educational background, knowledge of accounting, compliance information on the utilization of local government financial statements cities pekanbaru. Data was colleted by distributing questionnaires to the respondents. The population used in this study are staff / staff involved in the preparation of the budget, the number of samples taken at 96 people but the samples that can processed is 90 people. The data analysis technique used in this study is the technique of multiple regression analysis by using SPSS version 20.0. These results indicate the three variables that affect the utilization of local government financial statements and only one variable that does not have an influence on the utilization of local government financial statements . The result of this educational level, knowledge of accounting and compliace informastion have significantly effect on the utilization of local government financial statements . While educational background don’t have significantly effect on the utilization of local government financial statements.Keywords: Educational, Knowledge, Accounting, Compliance Information, and Government.